2019
DOI: 10.1088/1755-1315/268/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water cooled aluminium foam heat sink for concentrated photovoltaic solar cell

Abstract: Concentrated photovoltaic cell (CPV) is a popular renewable source nowadays. It has high efficient yet cost effective energy harvesting system available in the market. The performance of the CPV depends strongly on the temperature of the solar cell. The efficiency reduces as the surface temperature of the CPV increases. It is crucial to reduce the temperature of the CPV and maintains a small temperature variation along the surface of the CPV. Metal foam is an ideal solution for a CPV thermal management system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Due to its capacity to disperse heat in electronic chambers, this device has been utilized extensively by numerous authors to manage the thermal effect in solar panels. Cheong Tan et al [33] used aluminum foam in concentrated solar cells as a heat sink (CPV). Before inserting aluminum foam into a concentrated solar cell, the effects of porosity and pore density were initially studied to check for thermal performance.…”
Section: Pvt System In the Form Of Finmentioning
confidence: 99%
“…Due to its capacity to disperse heat in electronic chambers, this device has been utilized extensively by numerous authors to manage the thermal effect in solar panels. Cheong Tan et al [33] used aluminum foam in concentrated solar cells as a heat sink (CPV). Before inserting aluminum foam into a concentrated solar cell, the effects of porosity and pore density were initially studied to check for thermal performance.…”
Section: Pvt System In the Form Of Finmentioning
confidence: 99%
“…Numerous studies confirm their efficacy. (Cheong Tan et al, 2019) investigated the use of porous aluminium as a heat sink in concentrated photovoltaic (CPV) modules to improve heat dissipation. Their results showed that the porous aluminium significantly improved the heat dissipation and temperature of the CPV module.…”
Section: Introductionmentioning
confidence: 99%
“…High porosity metallic foams offer an excellent compromise between low density and lightweight, high surface area to volume [6], high elasticity and mechanical strength [7] and high heat dissipation with limited power and cost. The effective thermal conductivities of metallic opencell foams were found to vary depending on the nature of the material and the fluids circulating within them [8,9], and their level of porosity [10]. Aluminium foam effective thermal conductivity was measured to reach 6 W m −1 K −1 at 90.98% porosity [11][12][13] and with heat fluxes as high as 68.8 • 10 4 W m −2 when used as a heat sink [14].…”
Section: Introductionmentioning
confidence: 99%